1981
DOI: 10.1007/bf00432176
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on behavioral effects of an extract of Cannabis sativa L. in the rat

Abstract: The behavioral responses of the rat to an extract of Cannabis sativa were examined after IP injection of 5, 15 and 30 mg/kg (expressed as delta 9 tetrahydrocannabinol). The lowest dose of the extract induced stereotyped behavior (rhythmic head movements, intermittent gnawing and sniffing) together with hypersensitivity to stimuli and hyperthermia. The administration of higher doses of the extract resulted, initially, in similar behavioral effects but of greater intensity, followed by a cataleptic state alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Hyperresponsivity to auditory and tactile stimulation is also characteristic in both rats and mice (Dewey 1986;Ferri et al 1981). Although mildly restrained, a similar behavioral profile was noted in the present study and has been reported by others after acute AEA administration in rodents (Crawley et al 1993, Fride andSmith et al 1994, Stein et al 1996, Varga et al 1995.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hyperresponsivity to auditory and tactile stimulation is also characteristic in both rats and mice (Dewey 1986;Ferri et al 1981). Although mildly restrained, a similar behavioral profile was noted in the present study and has been reported by others after acute AEA administration in rodents (Crawley et al 1993, Fride andSmith et al 1994, Stein et al 1996, Varga et al 1995.…”
Section: Discussionsupporting
confidence: 89%
“…Catalepsy is a hallmark of both ⌬ 9 THC and AEA administration in rodents and can be generated after either peripheral (Ferri et al 1981;Pertwee 1972) or direct central administration into the caudate nucleus (Gough and Olley 1978), but not the globus pallidus (Pertwee and Wickens 1991). Although both the pallidum and caudate nuclei possess dense cannabinoid receptors (Herkenham et al 1991b), functional measures have yielded disparate results.…”
Section: Discussionmentioning
confidence: 99%
“…injection of AEA. This behavioural profile closely resembles the 'popcorn-like' hyper-reactive behaviour often reported in rodents when exposed to cannabinoids (Dewey, 1986;Ferri et al, 1981). The onset of these behavioural effects following an i.v.…”
Section: Discussionsupporting
confidence: 74%
“…A variety of centrally mediated phenomena have been observed in mouse, rat, dog, rabbit and monkey and are reviewed elsewhere (DEWEY 1986;HOLLISTER 1986;RAZDAN 1986), but include measures of spontaneous and forced (rotorod) locomotion, hypothermia, immobility, antinociception, drug discrimination, static ataxia, anticonvulsant actions and operant behavioral measures. Also, hypersensitivity to auditory or tactile stimulation has been observed (FERRI et al 1981). By defining the spectrum of activity (efficacy, potency, etc.)…”
Section: Unlearned Behaviors/ethologymentioning
confidence: 99%
“…Another well established motor effect of marihuana is its propensity to cause animals to maintain a rigid posture or catalepsy. Cataleptic effects of cannabinoids have been assessed both the bar immobility test (FERRI et al 1981) and the ring immobility test (PERTWEE 1972) . Clearly, the extrapyramidal system seems to play an important role in these effects.…”
Section: Motor Behaviormentioning
confidence: 99%